Hotel Lambert wobec wizyty cara Mikołaja I w Londynie w 1844 r. - Żurawski vel Grajewski, Radosław (Acta Universitatis Lodziensis. Folia Historica, 2001)
The visit of the tsar Nicholas I in London in 1844 was paid by the Russian monarch to reach two aims. First - to maintain the good relations between Great Britain and Russia which had existed since an agreement related to the Turco-Egyptian crisis in 1840 and to show to other European states that it still works. Second – to suggest the possibility of the partition of the Ottoman Empire and to investigate the readiness of the British government to advance such a policy. Of course the presence of the tsar in Great Britain gave an unique opportunity to the Polish emigrants in England and British society as well to manifest their feelings towards Nicholas I. The members of the Literary Association of the Friends of Poland in London and especially lord Dudley Coutts Stuart – the president of that Association and several ladies form British aristocracy – mainly the wives of the Whigs who were at that time in opposition towards governing Tory’s cabinet of Sir Robert Peel - organised the charitable ball for the Polish refugees just in the days of the tsar’s visit. All the Polish political parties in exile got united to proclaim a common manifest against the tsar. Lord Stuart and other Polish collaborators of the prince Adam Jerzy Czartoryski - the head of the monarcho–liberal camp of the Polish emigration (called Hotel Lambert) had tried to obtain from the Poles in London the promise of security for the tsar during his visit in Great Britain, but they failed. At first, Nicholas I met with a warm reception in British press, but soon it appeared that the British society was ready to manifest its cool feelings towards him. The public meeting against the tsar organised by the Chartists in High Holbom on Jun 6lh assembled several thousands people. During the Ascot-Races (horse-races) attended by the tsar he met the hostile cries of the crowd just the same as in the opera and in the streets of London. In a few days it was clear that his visit not only missed its political aims but failed on the field of propaganda as well. There is no doubt that Polish emigrants contributed to that second result of the visit.